Mechano-Chemical Coupling in Double Perovskites as Energy Related Materials. (28th July 2016) - Tsvetkov, Dmitry S.; Ivanov, Ivan L.; Malyshkin, Dmitry; Sereda, Vladimir V.; Zuev, Andrey Yu.
Abstract : Double perovskites R BaB2 O6-δ and Sr2 B MoO6, where R =rare-earth element and B = 3d -transition metal, with A -site and B -site, respectively, cation ordering are very promising materials for a variety of different devices for moderate high temperature applications such as solid oxide fuel cells (SOFCs) and mixed ionic and electronic conducting (MIEC) membranes. The unique feature of the oxides is their ability to undergo both thermal strain and that induced by the defects of oxygen nonstoichiometry in the oxide lattice. The latter is called as chemical or defect-induced strain. This property was shown recently to be anisotropic for tetragonal double perovskites unlike that for perovskites with pseudo-cubic structure. The crystal lattice of a double perovskite expands along a -axis and simultaneously contracts along c - axis with the decreasing lattice oxygen content. Expansion along a -axis was found to obey the model for pseudo-cubic oxides proposed by us earlier and based on relative change of mean ionic radius. The possible reasons for lattice contraction along c axis are discussed as well.